Cilvēku tirdzniecība - Dziedātāja, Madara (Latvijas Universitāte, 2008)
Cilvēku tirdzniecība uzskatām par vienu no transnacionālās organizētās noziedzības veidiem. Izvēloties tēmu bakalaura darbam krimināltiesībās, vēlējos rakstīt par to, kas aktuāls ir sabiedrībai. Cilvēku tirdzniecība ir nozīmīga problēma Latvijā un pasaulē. Cilvēku tirdzniecība pasaulē tiek uzskatīta par trešo ienesīgāko kriminālo biznesu pēc narkotiku un ieroču tirdzniecības. Ar katru gadu pieaug cilvēku tirdzniecības upuru skaits. Cilvēku tirdzniecības galvenais mērķis ir personas ekspluatācija. Latvijā atbildība par cilvēku tirdzniecību paredzēta Krimināllikuma 154.1 pantā un atbildība par personu nosūtīšanu seksuālai izmantošanai - Krimināllikuma 165.1 pantā. Rakstīt darbu krimināltiesībās par cilvēku tirdzniecību mudināja redzētais, ka cilvēki nezin un neapjauš problēmas būtību un risinājumus. Darba mērķis ir apskatīt cilvēku tirdzniecības krimināltiesisko raksturojumu, tiesu praksi, kā arī analizēt 154.1 panta, 165.1 panta noziedzīga nodarījuma sastāvu un kvalificējošās pazīmes.

Bachelor work is about regulation in trafficking of human beings in Latvia as it is an up – to date topic. The trafficking of people has become a global industry and serious transnational criminal phenomenon. Trafficking is organized criminal transportation of people within the country or abroad through the use of violence that is supported and implemented through purposeful actions on the part of individuals and organizations. In this project the main objectives are to look at the problem and make analysis of criminal regulation and jurisprudential precedents in human trafficking. My research draws on a wide variety sources, including laws, jurisdiction, monographies, materials prepared by multinational organizations and human rights reports. The term “human trafficking” is usually translated as trade in people. It is not an exact definition, because trafficking includes transportation, relocation, recruitment, hiding and commissioning. The key idea in definition is not so mach the fact of trade in persons as use of violence and fraud. Latvia is one of countries taking an active role in efforts to curb human trafficking; besides this process is clearly progressing. However, there is complacent attitude toward the phenomenon of human smuggling because trade of human beings is considered to be a serious type of crime, including complexity of this problem as a composite of a labour problem, illegal transplantation, and consequence of regional conflict within the country borders, illegal immigration and sexual exploitation. In criminal legislation of Latvia, there is regulation that defines the term human trafficking and provides punishment for such activities. Article 154.1 of The Criminal law makes human trafficking a crime, but article 165.1 focus on the sexual dimensions of human trafficking. These articles are in accordance with the international standards stipulated in The United Nation. In Latvia, there are official commentaries provided concerning implementation of the law. Courts generally rely on them in interpreting the law. To combat human trafficking effectively a comprehensive strategy needs to be developed and the crucial first step is to criminalizing trafficking of human beings. In some countries, there is no antitrafficking legislation. However, because of the difficulty in proving such cases, there is the lack of jurisprudential precedents. Analysis of jurisprudential precedents shows dissimilar understanding about qualification of crime. Criminal law is one of the most intrusive instruments in the hands of state authorities to recover, combat this problem and provide punishment. -
The trafficking of human beings
Keywords: Juridiskā zinātne